Fundamentals of industrial problem solving : a practitioner's guide /: a practitioner's guide. (2022) - Stefanov, Zdravko Ivanov; Livingston, Dana; Chauvel, J.P; Stefanov, Zdravko I; Herceg, Eldad; Schmidt, Carla; Chaudhary, Sunil Kumar; Christenson, Christopher Paul
No abstract available